Upstream Determinants and Downstream Risk Factors of COVID-19 Infection in Iran: A Qualitative Study of Health Professionals' Views - Zahra Jorjoran Shushtari; Marzieh Shirazikhah; Sina Ahmadi; Yahya Salimi; Akbar Biglarian; Ali Almasi; Toktam Paykani (Shiraz University of Medical Sciences, 2022)
Background: Iran, after China, emerged as one of the first COVID-19 epidemic countries. Despite all efforts to interrupt new transmission chains, the virus continued to quickly spread across the country. WHO has highlighted a crucial role for social factors and intersectoral collaboration to tackle COVID-19. This study aimed to identify challenges related to the upstream determinants and downstream risk factors of COVID-19 infection in Iran as perceived by health professionals at different levels of service administration. Methods: We conducted a qualitative study in October 2020. A directed qualitative content analysis was done to explore the views of health professionals and administrators toward determinants of COVID-19 infection in Iran. Using a deductive approach, we tested the implications of the WHO Commission on the Social Determinants of Health (CSDH) framework regarding COVID-19. Results: The determinants of COVID-19 infection in Iran are referred to as: 1) upstream social determinants, including political considerations in dealing with COVID-19, conflicting authority structures between and within organizations and sectors, poor intersectoral collaboration, unstable macroeconomic environment, pandemic crisis management, poor governance in the health system, cultural and societal values, trust and social capital, and individuals' socioeconomic status; and 2) downstream risk factors, including poor health literacy, poor compliance with COVID-19 prevention guidelines, secrecy related to the infection, individual's health status, lifestyle, and virus characteristics. Conclusion: It is essential to motivate people to practice preventive COVID-19 infection behaviors. To change the behavior at the population level, a complex fusion of policy and practice, and dealing with the complexity of structural determinants and downstream risk factors are needed.